Artificial intelligence in German SMES - barriers and challenges to Ai adoption in the German Mittelstand - Hopf, Valerie (2022)
Artificial intelligence (AI) is a crucialtechnology for the digital age, and therefore nations like Germany strive to become global AI leaders. As the backbone of Germany’s economy, this study focuses on small and medium-sized enterprises (SMEs) and their AI adoption level. Based on a convergent research design following the TOE framework, perceived barriers and challenges to AI adoption are examined. Results show that the majority of respondents plan to implement AI with in the next two years. However, the current adoption rate is only at 10.5%, primarily due to a lack of digitalization, human and IT resources as main barriers.